Angiotensin-converting Enzyme Degrades Alzheimer Amyloid β-Peptide (Aβ); Retards Aβ Aggregation, Deposition, Fibril Formation; and Inhibits Cytotoxicity - Jianguo Hu; Akira Igarashi; Makiko Kamata; Hachiro Nakagawa (2001)
We have demonstrated that the angiotensin-converting enzyme (ACE) genotype is associated with Alzheimer's disease (AD) in the Japanese population (1Hu J. Miyatake F. Aizu Y. Nakagawa H. Nakamura S. Tamaoka A. Takahashi R. Urakami K. Shoji M. Neurosci. Lett. 1999; 277: 65-67Crossref PubMed Scopus (69) Google Scholar). To determine why ACE affects susceptibility to AD, we examined the effect of purified ACE on aggregation of the amyloid β-peptide (Aβ)in vitro. Surprisingly, ACE was found to significantly inhibit Aβ aggregation in a dose response manner. The inhibition of aggregation was specifically blocked by preincubation of ACE with an ACE inhibitor, lisinopril. ACE was confirmed to retard Aβ fibril formation with electron microscopy. ACE inhibited Aβ deposits on a synthaloid plate, which was used to monitor Aβ deposition on autopsied brain tissue. ACE also significantly inhibited Aβ cytotoxicity on PC12 h. The most striking fact was that ACE degraded Aβ by cleaving Aβ-(1–40) at the site Asp7-Ser8. This was proven with reverse-phase HPLC, amino acid sequence analysis, and MALDI-TOF/MS. Compared with Aβ-(1–40), aggregation and cytotoxic effects of the degradation products Aβ-(1–7) and Aβ-(8–40) peptides were reduced or virtually absent. These findings led to the hypothesis that ACE may affect susceptibility to AD by degrading Aβ and preventing the accumulation of amyloid plaques in vivo. We have demonstrated that the angiotensin-converting enzyme (ACE) genotype is associated with Alzheimer's disease (AD) in the Japanese population (1Hu J. Miyatake F. Aizu Y. Nakagawa H. Nakamura S. Tamaoka A. Takahashi R. Urakami K. Shoji M. Neurosci. Lett. 1999; 277: 65-67Crossref PubMed Scopus (69) Google Scholar). To determine why ACE affects susceptibility to AD, we examined the effect of purified ACE on aggregation of the amyloid β-peptide (Aβ)in vitro. Surprisingly, ACE was found to significantly inhibit Aβ aggregation in a dose response manner. The inhibition of aggregation was specifically blocked by preincubation of ACE with an ACE inhibitor, lisinopril. ACE was confirmed to retard Aβ fibril formation with electron microscopy. ACE inhibited Aβ deposits on a synthaloid plate, which was used to monitor Aβ deposition on autopsied brain tissue. ACE also significantly inhibited Aβ cytotoxicity on PC12 h. The most striking fact was that ACE degraded Aβ by cleaving Aβ-(1–40) at the site Asp7-Ser8. This was proven with reverse-phase HPLC, amino acid sequence analysis, and MALDI-TOF/MS. Compared with Aβ-(1–40), aggregation and cytotoxic effects of the degradation products Aβ-(1–7) and Aβ-(8–40) peptides were reduced or virtually absent. These findings led to the hypothesis that ACE may affect susceptibility to AD by degrading Aβ and preventing the accumulation of amyloid plaques in vivo. Alzheimer's disease angiotensin-converting enzyme high performance liquid chromatography matrix-assisted laser desorption-time-of-flight/mass spectrometry amyloid precursor protein amyloid β-peptide phosphate-buffered saline bovine serum albumin phenylthiohydantoin renin-angiotensin system angiotensin Progressive cerebral dysfunction in Alzheimer's disease (AD)1 is accompanied by innumerable extracellular amyloid deposits in the form of senile plaque and microvascular amyloid. Amyloid protein is derived from the integral membrane polypeptide, β-amyloid precursor protein (βAPP). The released 39–43 residue amyloid β-peptide (Aβ) may subsequently undergo aggregation to form amyloid fibrils under the influence of various amyloid-associated factors (2Selkoe D.J. Annu. Rev. Neurosci. 1994; 17: 489-517Crossref PubMed Scopus (829) Google Scholar). The aggregation and deposition of Aβ has been linked to the toxic effects causing cell damage in AD. Because Aβ is present in both normal and AD subjects, an answer to the question of why Aβ accumulates in AD but not in the normal brain may lead to a possible cure for AD. Angiotensin-converting enzyme (ACE; dipeptidyl carboxypeptidase, EC3.4.15.1) is a membrane-bound ectoenzyme. It catalyzes the conversion of angiotensin I (AngI) to angiotensin II (AngII), which plays an important role in blood pressure and body fluid and sodium homeostasis (3Reid I.A. Am. J. Physiol. 1992; 262: E763-E778PubMed Google Scholar). The cloning of the ACE gene revealed a 287-bp insertion (I)/deletion (D) polymorphism in intron 16. The serum ACE activity of the ACE DD genotype was twice as high as that of the ACE II genotype (4Rigat B. Hubert C. Alhenc-Gelas F. Cambien F. Corvol P. Soubrier F. J. Clin. Invest. 1990; 86: 1343-1346Crossref PubMed Scopus (3524) Google Scholar). The ACE genotype is considered to be associated with hypertension, coronary artery disease, left ventricular hypertrophy, myocardial infarction, and diabetic nephropathy (5Abbud Z.A. Wilson A.C. Cosgrove N.M. Kosis J.B. Am. J. Cardiol. 1998; 81: 244-246Abstract Full Text Full Text PDF PubMed Scopus (33) Google Scholar, 6Ledru F. Blanchard D. Battaglis S. Jeunemaitre X. Courbon D. Guize L. Guermonprez J.L. Ducimetiere P. Diebold B. Am. J. Cardiol. 1998; 82: 160-165Abstract Full Text Full Text PDF PubMed Scopus (24) Google Scholar, 7Vleming L.J. van der Pijl J.W. Lemkes H.H. Westendorp R.G. Maassen J.A. Daha M.R. van Es L.A. van Kooten C. Clin. Nephrol. 1999; 51: 133-140PubMed Google Scholar). In particular, the ACE DD genotype is considered to be a risk factor for vascular diseases. We have compared the distribution of an I/D polymorphism of the gene coding for ACE in 133 Japanese sporadic AD patients and 257 control subjects (1Hu J. Miyatake F. Aizu Y. Nakagawa H. Nakamura S. Tamaoka A. Takahashi R. Urakami K. Shoji M. Neurosci. Lett. 1999; 277: 65-67Crossref PubMed Scopus (69) Google Scholar). The association between AD and ACE genotypes or alleles was found to be significant. The frequency of the ACE II genotype was 1.4× higher in AD than in controls, whereas that of ACE DD genotypes was only 0.4× as high. Moreover, the altered distribution of ACE alleles with AD patients appears to be independent of ApoE (1Hu J. Miyatake F. Aizu Y. Nakagawa H. Nakamura S. Tamaoka A. Takahashi R. Urakami K. Shoji M. Neurosci. Lett. 1999; 277: 65-67Crossref PubMed Scopus (69) Google Scholar). The association between AD and ACE genotypes was even more significant in the Japanese population than in the British population (8Kehoe P.G. Russ C. Mcllroy S. Williams H. Holmans P. Holmes C. Liolitsa D. Vahidassr D. Powell J. McGleenon B. Liddell M. Plomin R. Dynan K. Williams N. Neal J. Cairns N.J. Wilcock G. Passmore P. Lovestone S. Williams J. Owen M.J. Nat. Genet. 1999; 21: 71-72Crossref PubMed Scopus (240) Google Scholar). Although several reports published recently elucidate the association between ACE genotype and AD (9Alvarez R. Alvarez V. Lahoz C.H. Martinez C. Pena J. Sanchez J.M. Guisasola L.M. Salas Puig J. Moris G. Vidal J.A. Ribacoba R. Menes B.B. Uria D. Coto E. J. Neurol. Neurosurg. Psychiatry. 1999; 67: 733-736Crossref PubMed Scopus (87) Google Scholar, 10Crawford F. Abdullah L. Schinka J. Suo Z. Gold M. Duara R. Mullan M. Neurosci. Lett. 2000; 280: 215-219Crossref PubMed Scopus (56) Google Scholar, 11Farrer L.A. Sherbatich T. Keryanov S.A. Korovaitseva G.I. Rogaeva E.A. Petruk S. Premkumar S. Moliaka Y. Song Y.Q. Pei Y. Sato C. Selezneva N.D. Voskresenskaya S. Golimbet V. Sorbi S. Duara R. Gavrilova S. St. George-Hyslop P.H. Rogaev E.I. Arch. Neurol. 2000; 57: 210-214Crossref PubMed Scopus (94) Google Scholar), the mechanism of how ACE influences susceptibility to AD remains unclear. Here, we provide the first evidence that ACE significantly inhibits the aggregation, deposition, and cytotoxicity of Aβ in vitro by degrading Aβ-(1–40) at the site Asp7-Ser8. Somatic ACE was purified from human seminal plasma by using lisinopril-coupled Sepharose as described (12Kamata M. Hu J. Shibahara H. Nakagawa H. Int. J. Androl. 2001; 24: 225-231Crossref PubMed Scopus (10) Google Scholar). Immunoblotting was done with anti-somatic ACE antibodies as described (12Kamata M. Hu J. Shibahara H. Nakagawa H. Int. J. Androl. 2001; 24: 225-231Crossref PubMed Scopus (10) Google Scholar). Enzymatic activity of ACE was determined with the ACE color kit (Fujirebio, Japan) in whichp- hydroxyhippuryl-l-histidy-l-leucine was used as substrate (13Kasahara Y. Ashihara Y. Clin. Chem. 1981; 27: 1922-1925Crossref PubMed Scopus (254) Google Scholar). ACE activity was monitored by absorbance at 505 nm. Lisinopril was added to fixed amounts of PBS-diluted seminal plasma to the final concentrations described in the legend to Fig. 2. After incubation for 15 min at room temperature, ACE activities were determined. Synthetic Aβ (1–40, 1Hu J. Miyatake F. Aizu Y. Nakagawa H. Nakamura S. Tamaoka A. Takahashi R. Urakami K. Shoji M. Neurosci. Lett. 1999; 277: 65-67Crossref PubMed Scopus (69) Google Scholar, 2Selkoe D.J. Annu. Rev. Neurosci. 1994; 17: 489-517Crossref PubMed Scopus (829) Google Scholar, 3Reid I.A. Am. J. Physiol. 1992; 262: E763-E778PubMed Google Scholar, 4Rigat B. Hubert C. Alhenc-Gelas F. Cambien F. Corvol P. Soubrier F. J. Clin. Invest. 1990; 86: 1343-1346Crossref PubMed Scopus (3524) Google Scholar, 5Abbud Z.A. Wilson A.C. Cosgrove N.M. Kosis J.B. Am. J. Cardiol. 1998; 81: 244-246Abstract Full Text Full Text PDF PubMed Scopus (33) Google Scholar, 6Ledru F. Blanchard D. Battaglis S. Jeunemaitre X. Courbon D. Guize L. Guermonprez J.L. Ducimetiere P. Diebold B. Am. J. Cardiol. 1998; 82: 160-165Abstract Full Text Full Text PDF PubMed Scopus (24) Google Scholar, 7Vleming L.J. van der Pijl J.W. Lemkes H.H. Westendorp R.G. Maassen J.A. Daha M.R. van Es L.A. van Kooten C. Clin. Nephrol. 1999; 51: 133-140PubMed Google Scholar, 8–40) (Peptide Institute, Osaka, Japan) was dissolved first in dimethyl sulfoxide (Me2SO) and then in PBS to form the stock solution (1 mm Aβ containing 25% Me2SO). The stock solution was diluted 10-fold with PBS and incubated with or without ACE at 37 °C for 4 days. Aggregation of Aβ was measured by adding 10 μl of Aβ solution into 0.5 ml of thioflavine T (ThT) solution (final concentration: 3 μm in 50 mmsodium phosphate buffer, pH 6.0) and measuring the fluorescence intensity (λex at 450 nm, λem at 482 nm). Various concentrations of ACE were incubated with 10 nCi of 125I-Aβ (Amersham Biosciences) in 100 μl of TE buffer (50 mm Tris, pH 7.5, containing 0.1% BSA) at 37 °C for 3 h. Then the resulting solution was incubated in a Synthaloid Drug Screening Plate (Quality Controlled Biochemicals Inc.). The deposited Aβ was detected as radioactive signals according to the manufacturer's instructions. 100 μm Aβ solutions containing 2.5% Me2SO and preincubated with or without ACE and lisinopril (as prepared in the aggregation studies) were examined. The fibril-formed peptide in the solutions was adsorbed onto 200-mesh Formvar-coated copper grids and negative-stained with 2% uranyl acetate. The fibrils were observed with an electron microscope at 80 kV. Rat pheochromocytoma PC12 h cells were cultured in Dulbecco's modified Eagle's medium supplemented with 5% horse serum, 10% fetal calf serum, 2 mml-glutamine, and 100 units/ml penicillin/streptomycin at 37 °C under 5% CO2. For the neurotoxicity assay, cultured PC12 h cells were seeded onto a 96-well plate at a density of 104 cells/100 μl/well in a serum-free medium supplemented with 2 μm insulin. The cell counting kit-8 (Dojindo, Kumamoto, Japan) was used to measure the activities of dehydrogenase enzymes in living cells according to the manufacturer's instructions. Briefly, 10 μl of synthetic Aβ, preincubated with or without ACE, were added to each well. After incubation for 3 days, 10 μl of 5 mm WST-8 (2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium, monosodium salt) containing 0.2 mm1-methoxy-5-methyl-phenazinium-methyl-sulfate, and 150 mm NaCl was added to each well, followed by another hour of incubation. The WST-8 reduction was determined colorimetrically at 450 nm using an automatic microplate spectrophotometer. Fifty microliters of the reaction mixture was injected onto a TSK gel ODS120T column (0.64 × 25 cm, particle size 5 μm) and eluted at 1 ml/min with a linear gradient of 0∼80% acetonitrile, over a period of 50 min. The peaks monitored at 210 nm were collected. Microsequencing was performed automatically by a gas-liquid sequencer (Shimadzu, model PSQ1). Phenylthiohydantoin (PTH)-derivatives were identified by Shimadzu LC system PTH-1 on a Wakopak WS-PTH column (0.64 × 25 cm, particle size: 5 μm) with isocratic elution of the PTH-derivative mobile phase. The data were analyzed by a chromatopak CR4A data processor (Shimadzu). The HPLC eluates were dissolved in 50% acetonitrile, 0.1% trifluoroacetic acid. Aliquots of 0.5 μl were applied onto the MALDI target and allowed to air dry. All mass spectra were recorded with a Voyager-DE PRO mass spectrometer (Applied Biosystems, Japan) operated in the linear or reflection mode. MALDI-MS spectra were calibrated using several peaks as external standards. Obtained spectra were analyzed using the sequest algorithm with public data bases. Somatic ACE is present in serum and seminal plasma. We measured the ACE activity in human seminal plasma (844.84 ± 344.27 units/liter (n = 139)). 2M. Kamata and J. Hu, unpublished data. In contrast, normal human serum ACE activity has been reported to be 7.60 ± 2.01 units/liter (n = 173) (14Lieberman L. Am. J. Med. 1975; 59: 365-372Abstract Full Text PDF PubMed Scopus (765) Google Scholar). Because the activity in seminal plasma is over 100× higher than that in serum, we purified ACE from seminal plasma using the ACE inhibitor, lisinopril, as an affinity ligand. The purity of ACE eluted from the lisinopril-coupled Sepharose column was confirmed by electrophoregram. Purified ACE showed a single band with a molecular mass of 180 kDa using Coomassie Blue staining, and this band was strongly recognized by the anti-somatic ACE monoclonal antibody in immunoblotting (Fig.1). The purified ACE had an activity of about 20 unit/mg of protein that could be inhibited by lisinopril at a final concentration ranging from 10 to 0.01 μm in a dose response manner (Fig. 2). Synthetic Aβ in aqueous buffer tends to self-aggregate (15Hilbich C. Kisters-Woike B. Reed J. Masters C.L. Beyreuther K. J. Mol. Biol. 1991; 218: 149-163Crossref PubMed Scopus (538) Google Scholar, 16Terzi E. Holzemann G. Seelig J. J. Mol. Biol. 1995; 252: 633-642Crossref PubMed Scopus (297) Google Scholar), and only self-aggregated Aβ exerts cytotoxicity. We detected Aβ aggregation quantitatively using fluorescence of ThT, a reagent that associates rapidly with aggregated Aβ but not with monomeric or dimeric Aβ, giving rise to a new excitation absorption at 450 nm (17Levine H. Protein Sci. 1993; 2: 404-410Crossref PubMed Scopus (1955) Google Scholar). As shown in Fig.3, 100 μm Aβ solution aggregated remarkably after incubating at 37 °C for 4 days. When Aβ solution was incubated with ACE, the aggregation was significantly inhibited, and the inhibition was dose-dependent. A concentration of 240 milliunits/100 μl ACE reduced Aβ aggregation to about 20% of the control (p = 1.7 × 10−5 versus PBS). The presence of 2.5% Me2SO in the solution did not affect Aβ aggregation (data not shown). To elucidate whether the inhibition was specific, a final concentration of 10 μm of lisinopril, which could inhibit about 98% of ACE activity (Fig. 2), was added to the ACE solution 15 min before incubation with Aβ. As shown in Fig. 3, pretreatment with the ACE inhibitor blocked 99% of the inhibitory effect of ACE (p = 0.9 versus PBS), suggesting this inhibitory effect was based on the active site of the enzyme. As a negative control, BSA at double the concentration of ACE was added to the Aβ solution, but no significant alteration was observed (p = 0.5 versus PBS). Because the process of in vitro Aβ deposition at physiological concentrations onto plaques in AD brain preparations is cumbersome, Esler et al. (18Esler W.P. Stimson E.R. Ghilardi J.R. Felix A.M. Lu Y-A. Vinters H.V. Mantyh P.W. Maggio J.E. Nat. Biotechnol. 1997; 15: 258-263Crossref PubMed Scopus (80) Google Scholar) prepared a synthaloid (synthetic template) for Aβ deposition by immobilizing fibrillar Aβ in a polymer matrix. It was demonstrated that radiolabeled Aβ deposited onto synthaloid similar to plaques in AD brain (the natural template). We used synthaloid to predict the inhibition by ACE of Aβ deposition in autopsied AD brain preparations. The amount of 125I-Aβ deposited onto the plate was 3200 cpm. Addition of 240 milliunits of ACE reduced the deposition to 1648 cpm, approximately half of the control (Fig. 4). ACE remarkably inhibited the 125I-Aβ deposition in a dose-dependent manner. Fibril formation of Aβ was investigated by electron microscopy (Fig.5). Abundant amyloid fibrils were found in the incubated Aβ solution (100 μm; containing 2.5% Me2SO). In contrast, very few fibrils were observed in the Aβ solution incubated with 240 milliunits of ACE. Compared to other rat and human cell types of neuronal origin, the rat pheochromocytoma PC12 h cell was found to be the most sensitive to Aβ (19Shearman M.S. Ragn C.I. Iversen L.L. Proc. Natl. Acad. Sci. U. S. A. 1994; 91: 1470-1474Crossref PubMed Scopus (425) Google Scholar). A novel cell proliferation and cytotoxicity assay method using a tetrazolium salt that produces a water-soluble formazan dye was reported. The new method was able to measure the dehydrogenase enzymes in living cells in a more convenient and sensitive way than the most currently utilized 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) methods (20Ishiyama M. Tominaga H. Shiga M. Sasamoto K. Ohkura Y. Ueno K. Watanabe M. In Vitro Toxicol. 1995; 8: 187-190Google Scholar, 21Ishiyama M. Miyazono Y. Sasamoto K. Ohkura Y. Ueno K. Talanta. 1997; 44: 1299-1305Crossref PubMed Scopus (540) Google Scholar). We therefore used the PC12 h cell and the new cytotoxicity assay to evaluate the inhibitory effect of ACE on Aβ cytotoxicity. As shown in Fig. 6, incubation of 10 μm aggregated Aβ with PC12 h cells for 3 days caused 53% cell death, while preincubation with 240 milliunits of ACE increased cell survival to 80 ± 5.2% (p = 0.02versus PBS). Similarly, 160 and 60 milliunits of ACE resulted in cell survival to 65 ± 0.7% (p = 0.0001 versus PBS) and 60 ± 0.2% (p = 0.008 versus PBS), respectively. The effect of ACE on PC12 h cell survival was dose-dependent and was significantversus controls. Preincubation of double the amount of BSA, instead of ACE, did not affect cell survival (50 ± 1%). On the other hand, ACE treated with 10 μm lisinopril significantly blocked the inhibitory effect of ACE on Aβ cytotoxicity, resulting in the reduction of 57 ± 2% (p = 0.005 versus ACE (240 milliunits)). These data suggest that the inhibitory effect on Aβ cytotoxicity was a specific effect by ACE. To investigate the reason ACE affected Aβ aggregation and cytotoxicity, we tried to determine if any degradation occurred during the incubation of Aβ-(1–40) with ACE and discovered a new degraded fragment using an HPLC chromatogram (Fig.7). The degraded fragment was eluted at a more hydrophobic region compared with Aβ-(1–40) (Fig. 7,A and B). Amino acid sequence analysis showed that the first ten residues of the degraded fragment (Fig. 7 A, peak b) was SGYEVHHQKL, which corresponded to Aβ-(8–17). The elution time of the degraded fragment coincided with that of the synthetic Aβ-(8–40) peptide (Fig. 7, A and C). To confirm that the degraded fragment is Aβ-(8–40), we examined the molecular weight of the synthetic Aβ-(8–40) and the degraded fragment using MALDI-TOF/MS spectroscopy. Our results for Aβ-(8–40) show 3457.78 and for the degraded peptide, 3457.98 (data not shown). These data suggest that ACE cleaved the Asp7-Ser8 linkage of Aβ-(1–40) during the incubation of Aβ with ACE. To determine the fate of another degraded fragment Aβ-(1–7), we incubated Aβ-(1–7) with ACE. The HPLC plot revealed that Aβ-(1–7) was further degraded. The Aβ-(1–7) peak (Fig. 7 D) disappeared after incubation with ACE and was replaced by three small peaks (Fig. 7 E). The three small peaks could also be detected after incubating Aβ-(1–40) with ACE (Fig.7 A). Aggregation and cytotoxic effects of the degradation products were investigated simultaneously with Aβ-(1–40). Aβ-(1–7)showed neither an aggregation nor a cytotoxic effect. Aβ-(8–40) gave an aggregation effect of 35.7%, which was significantly lower than that of Aβ-(1–40). The level of aggregation of Aβ-(8–40) incubated with Aβ-(1–7) was not significantly different from that of Aβ-(8–40) alone (Fig. 8). As shown in Fig. 9, PC12 h cells incubated with Aβ-(8–40) for 3 days exhibited a reduced survival to 77 ± 3%, which was significantly higher than that seen with Aβ-(1–40) (p = 0.004versus PBS).Figure 9Cytotoxicity of Aβ degradation products. Ten microliters of synthetic Aβ-(1–40) or Aβ-(8–40) or Aβ-(1–7) solution was added to 104 PC12 h cells as described in the legend to Fig. 6. After 3 days, the living cells were detected with the cell count kit. The values are the means ± S.D. (n = 3). *, p < 0.05; **, p < 0.01; ***, p < 0.001.View Large Image Figure ViewerDownload Hi-res image Download (PPT) Schachter et al. (22Schachter F. Faure-Delanef L. Guenot F. Rouger H. Froguel P. Lesueur-Ginot L. Cohen D. Nat. Genet. 1994; 6: 29-32Crossref PubMed Scopus (920) Google Scholar) reported that ACE polymorphism was associated with human longevity and that the ACE DD genotype was surprisingly increased in centenarians. Therefore, Kehoe et al. (8Kehoe P.G. Russ C. Mcllroy S. Williams H. Holmans P. Holmes C. Liolitsa D. Vahidassr D. Powell J. McGleenon B. Liddell M. Plomin R. Dynan K. Williams N. Neal J. Cairns N.J. Wilcock G. Passmore P. Lovestone S. Williams J. Owen M.J. Nat. Genet. 1999; 21: 71-72Crossref PubMed Scopus (240) Google Scholar) hypothesized that the D allele might protect against the development of AD and actually confirmed the hypothesis in British populations. We have reported that the ACE genotype is associated with AD in Japanese population even more significantly than that in the British population reported by Kehoe et al. (1Hu J. Miyatake F. Aizu Y. Nakagawa H. Nakamura S. Tamaoka A. Takahashi R. Urakami K. Shoji M. Neurosci. Lett. 1999; 277: 65-67Crossref PubMed Scopus (69) Google Scholar). Recently, a gender-specific association of the ACE genotype with AD in the female clinic population was reported (10Crawford F. Abdullah L. Schinka J. Suo Z. Gold M. Duara R. Mullan M. Neurosci. Lett. 2000; 280: 215-219Crossref PubMed Scopus (56) Google Scholar). It was also reported that ApoE and ACE genotypes might be independent risk factors for late-onset AD in both Russian and North American populations (11Farrer L.A. Sherbatich T. Keryanov S.A. Korovaitseva G.I. Rogaeva E.A. Petruk S. Premkumar S. Moliaka Y. Song Y.Q. Pei Y. Sato C. Selezneva N.D. Voskresenskaya S. Golimbet V. Sorbi S. Duara R. Gavrilova S. St. George-Hyslop P.H. Rogaev E.I. Arch. Neurol. 2000; 57: 210-214Crossref PubMed Scopus (94) Google Scholar). Although several clinical, epidemiological, and pathological observations suggested that vascular risk factors might be associated with cognitive performances of AD, the mechanism by which the ACE genotypes influenced susceptibility to AD was unknown. The recent studies on the renin-angiotensin system (RAS) of the mammalian brain may explain the association between ACE and AD in a certain sense. Besides the classical RAS, a local RAS in the brain may play a critical role in the central nervous system. It has been reported that angiotensin in astrocytes is required for the functional maintenance of the blood brain barrier (23Kakinuma Y. Hama H. Sugiyama F. Yagami K. Goto K. Murakami K. Fukamizu A. Nat. Med. 1998; 4: 1078-1080Crossref PubMed Scopus (124) Google Scholar), which is impaired in AD (24Skoog I. Wallin A. Fredman P. Neurology. 1998; 50: 966-971Crossref PubMed Scopus (212) Google Scholar). Central RAS prevents neuronal cells from apoptosis not only by AngII but also by AngIV, an AngII metabolite (25Kakinuma Y. Hama H. Sugiyama F. Goto K. Murakami K. Fukamizu A. Neurosci. Lett. 1997; 232: 167-170Crossref PubMed Scopus (43) Google Scholar). Both AngII and AngIV excite hippocampal neuronal activity (26Albrecht D. Broser M. Kruger H. Regul. Pept. 1997; 70: 105-109Crossref PubMed Scopus (35) Google Scholar) and regulate cerebral blood flow (27Kramar E.A. Harding J.W. Wright J.W. Regul. Pept. 1997; 68: 131-138Crossref PubMed Scopus (118) Google Scholar). Colocalization of ACE and AngI receptor in the substantia nigra, the caudate nucleus, and putamen of human and rat suggests central RAS may be important in modulating central dopamine release. In Parkinson's disease, there is a marked reduction of ACE receptors associated with the nigrostriatal dopaminergic neuron loss, and ACE inhibitor modifies the clinical features of Parkinson's disease (28Zhuo J. Moeller I. Jenkins T. Chai S.Y. Allen A.M. Ohishi M. Mendelsohn F.A. J. Hypertens. 1998; 16: 2027-2037Crossref PubMed Scopus (113) Google Scholar). The striking distribution of AngIV receptors in cholinergic neurons, motor, and sensory nuclei of the brain suggest that AngIV plays an important role in the facilitation of learning and memory (29Reardon K.A. Mendelsohn F.A. Chai S.Y. Horne M.K. Aust. N Z. J. Med. 2000; 30: 48-53Crossref PubMed Scopus (103) Google Scholar, 30Wright J.W. Stubley L. Pederson E.S Kramar E.A. Hanesworth J.M. Harding J.W. J. Neurosci. 1999; 19: 3952-3961Crossref PubMed Google Scholar, 31Pederson E.S. Harding J.W. Wright J.W. Regul. Pept. 1998; 74: 97-103Crossref PubMed Scopus (98) Google Scholar). These studies demonstrate that angiotensin is essential not only to the circulatory system, but also to the central nervous system. Although these results are helpful in understanding the relationship between AD and ACE, they do not provide direct evidence. AD is a heterogeneous disorder with a variety of molecular pathologies converging predominantly on abnormal amyloid deposition particularly in the brain. Aβ aggregation into senile plaques is an important pathological hallmark of AD. We hypothesize that ACE may affect Aβ aggregation and deposition in the brain. We have substantiated the hypothesis and elucidate here that ACE inhibits Aβ aggregation, deposition, fibril formation, and cytotoxicity in vitro. These results provide the first evidence of direct involvement of ACE with AD susceptibility. Several lines of evidence have shown that amorphous, largely nonfilamentous deposits of Aβ (so called "diffuse" or preamyloid plaques) precede the development of fibrillar amyloid, dystrophic neurites, neurofibrillary tangles, and other cytopathological changes in Down's syndrome and AD. In the AD brain, diffuse plaques composed mostly of amorphous Aβ are inert, whereas compact plaques composed of Aβ fibrils are associated with neurodegenerative changes (32Selkoe D.J. Yamazaki T. Citron M. Podlisny M.B. Koo E.H. Teplow D.B. Haass C. Ann. New York Acad. Sci. 1996; 777: 57-64Crossref PubMed Scopus (224) Google Scholar, 33Lorenzo A. Yankner B.A. Ann. New York Acad. Sci. 1996; 777: 89-95Crossref PubMed Scopus (136) Google Scholar).In vitro experiments also reveal that the neurotoxicity of Aβ is associated with their ability to form stable aggregates in aqueous solution (34Yanker B.A. Neurobiol. Aging. 1992; 13: 615-616Crossref PubMed Scopus (43) Google Scholar, 35Pike C.J. Burdick D. Walencewicz A.J. Glabe C.G. Cotman C.W. J. Neurosci. 1993; 13: 1676-1687Crossref PubMed Google Scholar, 36Pike C.J. Walencewicz A.J. Glabe C.G. Cotman C.W. Brain Res. 1991; 563: 311-314Crossref PubMed Scopus (825) Google Scholar). The aggregation of Aβ only is not sufficient to exert neurotoxicity effect, but further amyloid fibril formation is required (37Lorenzo A. Yankner B.A. Proc. Natl. Acad. Sci. U. S. A. 1994; 91: 12243-12247Crossref PubMed Scopus (1298) Google Scholar). Aggregation of Aβ is template-independent initial nidus formation, and deposition of Aβ is template-dependent subsequent to plaque growth. These are considered fundamentally distinct biochemical processes in AD (38Esler W.P. Stimson E.R. Ghilardi J.P. Vinters H.V. Lee J.P. Mantyh P.W. Maggio J.E. Biochemistry. 1996; 35: 749-757Crossref PubMed Scopus (124) Google Scholar). Taken together, these findings suggest that aggregation, deposition, and fibril formation are the necessary processes for Aβ to achieve and strengthen a neurotoxic state. Just in these critical processes, ACE plays an important role in decrease of Aβ neurotoxicity, suggesting the possible cause of ACE genotype in affecting susceptibility to AD. Three types of proteases, which are designated α-, β-, and γ-secretases, cleave APP. Processing by α-secretase cleaves within the Aβ sequence whereas β- and γ-secretase cleaves on the N- and C-terminal ends of the Aβ region, respectively, releasing Aβ (39Mills J. Reiner P.B. J. Neurochem. 1999; 72: 443-460Crossref PubMed Scopus (208) Google Scholar). γ-Secretase cleaves at several adjacent sites to yield Aβ species containing 39–43 amino acid residues. Because α-secretase destroys the Aβ sequence, it is generally thought that α-secretase pathway mitigates amyloid formation, although this has not yet been demonstrated unequivocally (40Nunan J. Small D.H. FEBS Lett. 2000; 483: 6-10Crossref PubMed Scopus (422) Google Scholar). In addition, the C-terminally truncated form of APP released by α-secretase may have trophic actions (41Small D.H. Neurochem. Res. 1998; 23: 795-806Crossref PubMed Scopus (31) Google Scholar), which could antagonize the neurotoxic effects of aggregated Aβ (42Mok S.S. Clippingdale A.B. Beyreuther K. Masters C.L. Barrow C.J. Small D.H. J. Neurosci. Res. 2000; 61: 449-457Crossref PubMed Scopus (14) Google Scholar). ACE acts like the α-secretase in degrading Aβ and thus preventing aggregation. Several Aβ-degrading enzymes were studied because of their potential usage in AD treatment. BACE can cleave full-length APP at Asp1 of the Aβ sequence and also at Glu11(42Mok S.S. Clippingdale A.B. Beyreuther K. Masters C.L. Barrow C.J. Small D.H. J. Neurosci. Res. 2000; 61: 449-457Crossref PubMed Scopus (14) Google Scholar). Recently, Chesneau et al. (43Chesneau V. Vekrellis K. Rosner M.R. Selkoe D.J. Biochem. J. 2000; 351: 509-516Crossref PubMed Scopus (84) Google Scholar) reported that insulin-degrading enzyme (IDE) is sufficient to degrade Aβ and that its degradation products do not promote oligomerization of the intact Aβ peptide (43Chesneau V. Vekrellis K. Rosner M.R. Selkoe D.J. Biochem. J. 2000; 351: 509-516Crossref PubMed Scopus (84) Google Scholar). Iwata et al. (44Iwata N. Tsubuki S. Takaki Y. Watanabe K. Sekiguchi M. Hosoki E. Kawashima Morishima M. Lee H.J. Hama E. Aizawa S., Y. Saido T.C. Nat. Med. 2000; 6: 143-150Crossref PubMed Scopus (0) Google Scholar) reported that endopeptidase 24.11 (neprylisin) is involved selectively in the catabolism of Aβ-(1–42) in rat brain parenchyma. Yu et al. (45Yu G.S.P. Hu J. Nakagawa H. Neurosci. Lett. 1998; 254: 125-128Crossref PubMed Scopus (27) Google Scholar) reported that midkine formed complexes with Aβ-(1–40) and protected PC12 h from Aβ-induced cytotoxicity. In the present study, we report that ACE is a new Aβ-degrading enzyme that cleaves the Aβ sequence at Asp7-Ser8. The cleavage site is different from the site that converts AngI to AngII, or other Aβ-cleaving sites reported as yet. Although the actual meaning of a real Aβ-degrading function of ACE in vivo remains to be further studied, our data strongly lead to the hypothesis that ACE may affect susceptibility to AD by degrading Aβ and preventing the accumulation of amyloid plaques in the brains of AD patients.